Ketone Body Metabolism in the Ischemic Heart - Kolwicz, Stephen C. (Frontiers in Cardiovascular Medicine, 2021)
Ketone bodies have been identified as an important, alternative fuel source in heart failure. In addition, the use of ketone bodies as a fuel source has been suggested to be a potential ergogenic aid for endurance exercise performance. These findings have certainly renewed interest in the use of ketogenic diets and exogenous supplementation in an effort to improve overall health and disease. However, given the prevalence of ischemic heart disease and myocardial infarctions, these strategies may not be ideal for individuals with coronary artery disease. Although research studies have clearly defined changes in fatty acid and glucose metabolism during ischemia and reperfusion, the role of ketone body metabolism in the ischemic and reperfused myocardium is less clear. This review will provide an overview of ketone body metabolism, including the induction of ketosis via physiological or nutritional strategies. In addition, the contribution of ketone body metabolism in healthy and diseased states, with a particular emphasis on ischemia-reperfusion (I-R) injury will be discussed.